Identifikasi dan Uji Aktivitas Antioksidan Senyawa Metabolit Sekunder Ekstrak Tanaman Cleome viscosa L: Identification and Antioxidants Activity Tests of Secondary Metabolite Compounds of Clome viscosa L. Plant Extracts - Imran; Nohong; Ruslan; Laily Nurliana; Muh. Natsir; La Ode Abd Kadir; La Rudi; Thamrin Azis (KOVALEN: Jurnal Riset Kimia, 2023)
Cleome viscosa L. has been used empirically by people on the island to treat diseases that have clinical symptoms such as malaria (fever, sweating, chills, and muscle aches). The purpose of this study was to determine the class of secondary metabolites and antioxidant activity. The extraction was carried out using the maceration method, while the fractionation was carried out using the separating funnel. The secondary metabolites found in the Cleome viscosa L. plant extract are alkaloids, flavonoids, steroids, terpenoids, tannins, and saponins. Antioxidant test conducted by DPPH method showed that the positive control of ascorbic acid and methanol extract obtained IC50 values of 3.86 ppm and 37.4 ppm, respectively.